Istirâtîjiyyât al-Wa’yi al-Mîtâ’irfânî Al-Qirâî li al-Muqarrarât ad-Dirâsiyyah ladâ Muta’allimî al-Lughah al-‘Arabiyyah Lughah Tsâniyyah - Nouroudine Abdoulaye Mamoudou (Jurnal Internasional Pendidikan Bahasa Arab, 2022)
This study aimed to investigate the students' strategies of the metacognition awareness for the academic texts reading. The study was attended by (31) students of different nationalities, in the third and fourth levels. To collect the data, we used a questionnaire containing (31) items, divided into three categories: general reading strategies, problem-solving strategies and support strategies. The data collected has been analyzed by using SPSS. The results shown that, the problem-solving strategies came with the highest arithmetic mean value with (3.62), then the support strategies to a height degree of (3.54) mean value, and finally, the global reading strategies, with a medium mean degree of (3.39). The overall results, which came to a large height degree (3.51), indicate that the students' awareness of metacognitive reading strategies is to a high degree. Regarding to the results, the study recommend researcher to conducting a similar study on the female student, individually, or in partnership with the male students, to find out which gender is more aware of metacognitive-reading strategies.